The Restitutionary Aftermath of Contractual Illegality - YIP, Man (Institutional Knowledge at Singapore Management University, 2015)
This article critically analyses the mess of illegality in one specific area: the restitutionary aftermath of illegal contracts where the illegality is sourced in a statute. Its chief objective is to identify the real sources of difficulty underlying this area of the law so as to pave the way for meaningful reform. Two main reflections are offered. First, examining the case law, it points out that insufficient attention has been paid to various factors, including: the interface of common law rules and statute; the inexact science of statutory construction; different emerging methodologies in determining consistency; the rise of unjust enrichment and its impact on the evaluation of policy considerations. Mess and confusion regarding availability of restitutionary relief will persist unless these issues are addressed, although not all could be resolved. Second, regarding the structural analysis of the restitutionary claim, it argues that the question of whether “illegality” can operate as an unjust factor is more multi-faceted than at first sight appears. It also argues that English law should allow concurrent grounds for restitution.